AKUNTANSI FORENSIK SEBAGAI GARDA TERDEPAN ANTI FRAUD - Diah Ayu Gustiningsih; Riza Praditha; Muhammad Dasri (Komunitas Manajemen Kompetitif, 2026)
The rapid advancement of information technology has given rise to increasingly complex forms of digital-based financial fraud (cyber fraud) that are difficult to detect through conventional audit approaches. This condition necessitates a more adaptive role of forensic accounting as an anti-fraud safeguard within modern business and organizational environments. This study aims to analyze the role and objectives of forensic accounting in detecting and preventing cyber fraud, as well as to examine the importance of strengthening forensic accounting competencies in addressing digital fraud challenges. The research employs a literature review method using a systematic synthesis approach of reputable national and international journal articles relevant to forensic accounting and cyber fraud. The findings indicate that forensic accounting plays a strategic role not only in post-fraud investigations but also in early detection and prevention of technology-based fraud. The effectiveness of this role is strongly influenced by the mastery of forensic accounting competencies, including accounting expertise, auditing skills, data analytics, and digital forensic capabilities. The results underscore that strengthening forensic accounting competencies is a key factor in enhancing organizational capacity to mitigate cyber fraud risks. This study is expected to contribute theoretically to the development of forensic accounting literature and provide practical implications for organizations and educational institutions in responding to the challenges of digital fraud.